Electrons and disorder in solids - Gantmakher, V.F. (Clarendon Press,Oxford University Press, 2005)
This book has been written for those who study or professionally deal with solid state physics. It contains modern concepts about the physics of electrons in solids. It is written using a minimum of mathematics. The emphasis is laid on various physical models aimed at stimulating creative thinking. The book helps the reader choose the most efficient scheme of an experiment or the optimal algorithm of a calculation. Boltzmann and hopping types of conductivity are compared. The qualitative theory of weak localization is presented and its links with the true localization and metal-insulator transitions. Processes that determine the structure of impurity bands are revealed. The concepts introduced in this book are applied to descriptions of granular metals and quasicrystals, as well as the integer quantum Hall effect, emphasizing their universality